Transmission of Cricket paralysis virus via exosome-like vesicles during infection of Drosophila cells. Issue 1 (December 2018) - Kerr, Craig; Dalwadi, Udit; Scott, Nichollas; Yip, Calvin; Foster, Leonard; Jan, Eric
Abstract Viruses are classically characterized as being either enveloped or nonenveloped depending on the presence or absence of a lipid bi-layer surrounding their proteinaceous capsid. In recent years, many studies have challenged this view by demonstrating that some nonenveloped viruses (e.g. hepatitis A virus) can acquire an envelope during infection by hijacking host cellular pathways. In this study, we examined the role of exosome-like vesicles (ELVs) during infection ofDrosophilia melanogaster S2 cells by Cricket paralysis virus (CrPV). Utilizing quantitative proteomics, we demonstrated that ELVs can be isolated from both mock- and CrPV-infected S2 cells that contain distinct set of proteins compared to the cellular proteome. Moreover, 40 proteins increased in abundance in ELVs derived from CrPV-infected cells compared to mock, suggesting specific factors associate with ELVs during infection. Interestingly, peptides from CrPV capsid proteins (ORF2) and viral RNA were detected in ELVs from infected cells. Finally, ELVs from CrPV-infected cells are infectious suggesting that CrPV may hijack ELVs to acquire an envelope during infection of S2 cells. This study further demonstrates the diverse strategies of nonenveloped viruses from invertebrates to vertebrates to acquire an envelope in order to evade the host response or facilitate transmission.